If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying -6X + 4 = 7X + 121 Reorder the terms: 4 + -6X = 7X + 121 Reorder the terms: 4 + -6X = 121 + 7X Solving 4 + -6X = 121 + 7X Solving for variable 'X'. Move all terms containing X to the left, all other terms to the right. Add '-7X' to each side of the equation. 4 + -6X + -7X = 121 + 7X + -7X Combine like terms: -6X + -7X = -13X 4 + -13X = 121 + 7X + -7X Combine like terms: 7X + -7X = 0 4 + -13X = 121 + 0 4 + -13X = 121 Add '-4' to each side of the equation. 4 + -4 + -13X = 121 + -4 Combine like terms: 4 + -4 = 0 0 + -13X = 121 + -4 -13X = 121 + -4 Combine like terms: 121 + -4 = 117 -13X = 117 Divide each side by '-13'. X = -9 Simplifying X = -9
| 5x-7(0)=-18 | | k=0 | | 5(0)-7y=-18 | | 7X+1=121-5X | | (q^2+5q+4)(q^2-1)+q^3-q=2q+2q^2-2 | | -4X+10=21+7X | | 3x-6(0)=-7 | | 3(0)-6y=-7 | | 2=-1x+45-8 | | 2=-1x+45 | | 2=-1x+9 | | 2=-1x+4 | | 3-4X=-2X+17 | | -2-8x=0 | | 4X+3=7X-12 | | -1-8x=0 | | w^2+12w+40=0 | | 4X+8=29-3X | | 4k+5=11-2k | | 7=-z+9 | | 25x^2-10x+1=0e | | 7X+2=128-7X | | 7-2(3x+2)=3x+4(x-9) | | s^2+3s-4=s^2+6s+9 | | 6-23=7x-4-6x | | 7x-6x+13=12-5 | | m=-2+5k | | 16x^2-324=0 | | -0.5x^2+176x-1440=12000 | | 4x^2-12x-72=0 | | -0.5x^2+176x-1440=0 | | 2i+8=18 |